Anaphylaxis following a transvaginal ultrasound. Issue 1 (December 2016) - Jakubovic, Baruch; Saperia, Corey; Sussman, Gordon
Abstract Polyethylene glycol is a ubiquitous, water-soluble, organic compound found in a wide variety of commercially available products. While generally a benign substance, in rare instances, it can induce hypersensitivity reactions. Herein, we describe a case of anaphylaxis to polyethylene glycol-containing lubricating gel used for a transvaginal ultrasound. This case highlights the importance of early recognition of a rare cause of anaphylaxis that may occur in the health-care setting. It is of particular importance given the widespread use of similar lubricating materials in multiple practice settings for the use of internal examinations and ultrasonography.